METHODOLOGICAL APPROACHES TO ORGANIZATION OF SAFE INFORMATION AND EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY - A. N. Privalov; Yu. I. Bogatyreva; V. A. Romanov (Russian State Vocational Pedagogical University, 2017)
Introduction. One of the tendencies of modern higher education is the ubiquitous use of information and communication technologies. At the same time, the functioning of the electronic information and educational environment (IEE) of the university should be based on the means of IEE and the condition of its information security.The aim of the research is conceptualization of a problem of the rational organization of the safe information and education environment of higher education institution wherein reliable protection of its infrastructure, the personal and unique information of a pupil and teacher and virtual space of their educational interaction is provided.Methodology and research methods. System-based approach is a key approach to organization of safe educational environment of the university. From the point of view of authors, personal-activity and functional approaches are expedient while designing and development of a safe IEE. Socio-historical and theoretical-methodological analysis, modeling, research and synthesis of experience of effective application of the systems approach in educational professional organizations are used.Results and scientific novelty. The concept «safe information educational environment of the university» is specified wherein the first word has to express a predominant quality of the system. Creating a safe information environment in educational professional organizations provides a convenient and safe educational environment in the process of professional training of university students. The components and directions for the organization of the safe IEE are highlighted. Practical recommendations for its design and successful functioning are given.Practical significance. The materials of the present research can be demanded by managers and administrative employees of educational organizations.